Data Analysis of the Authenticity of the National Anthems and Turkish National Anthem - Kiliç, Günay; Budak, İbrahim; Haşiloğlu, Selçuk Burak (Pamukkale University, 2022)
National anthems are one of the indicators of independence of countries and talk about the sense of independence of countries. In this study, the National Anthem of the Republic of Turkey, Turkish National Anthem, is analyzed by data mining techniques.
While analyzing Turkish National Anthem, the anthems of the member states of the Turkic Council with which they have a common language tie, the anthems of the member states of the Organization of Islamic Cooperation, which are thought to have common religious values, and the anthems of the European Union Member States, since Turkey is a European country, were included in the analysis.
The analysis includes cluster analysis and association analysis techniques in terms of data mining. In terms of text mining, the similarities of Turkish National Anthem and other national anthems were examined in terms of word size, title size and sentiment analysis. As a result of the analysis, all the country anthems that were compared in one cluster, whose data were calculated as two clusters by cluster analysis, were included, while Turkish National Anthem took place alone in the other cluster. This is an important indicator in revealing the originality of Turkish National Anthem. Again, the analyzes in 3 dimensions under the title of text mining did not reveal a similarity between Turkish National Anthem and the national anthems compared. The results of the association analysis are important in terms of showing the use of common words and words in national anthems together.
Keywords: Milli marşlar; Gizli Ayırma Tahsisi; Duygu Analizi; Kümeleme Analizi; Birliktelik Analizi; National anthems; Latent Dirichlet Allocation; Sentiment Analysis; Cluster Analysis; Association Rule Analysis; 16. Peace & justice